Unintentional boron incorporation in AlGaN layers grown by plasma-assisted MBE using highly efficient nitrogen RF plasma-sources - Novikov, Sergei V.; Foxon, C.T. (Elsevier, 2017)
Plasma-assisted molecular beam epitaxy (PA-MBE) is now widely used for the growth of group III-nitrides. Many years ago it became clear that during PA-MBE there is unintentional doping of GaN with boron (B) due to decomposition of the pyrolytic boron nitride (PBN) cavity of the RF plasma source. In this paper we discuss the unintentional B incorporation for PA-MBE growth of GaN and AlxGa1−xN using a highly efficient RF plasma source. We have studied a wide range of MBE growth conditions for GaN and AlxGa1−xN with growth rates from 0.2 to 3 µm/h, RF powers from 200 to 500 W, different nitrogen flow rates from 1 to 25 sccm and growth times up to several days. The chemical concentrations of B and matrix elements of Al, Ga, N were studied as a functions of depth using secondary ion mass spectrometry (SIMS). We demonstrate that boron incorporation with this highly efficient RF plasma source is approximately 1×1018 to 3×1018 cm−3 for the AlxGa1−xN growth rates of 2 – 3 µm/h.